"Self-filling" of Vasyl Stus in the context of the mankind spiritual transformation (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article Onikienko Inni deals with the "self-fulfillment" of Vasyl Stus as his poetical credo. His original philosophy comes out of "the philosophy of the heart" by Grygoriy Skovoroda, the creation of the self as "great entelechies" by Johann Wolfgang von Goethe, Christian intitiation rituals and the eastern philosophy of sufism.  The author researches the expression of this aethetical-philosophical position on the thematic, imagerial-symbolic and lexical levels of the collection of poems "Creativity Time".
Keywords: “filling of yourself”; “initiation”; Sufism; entelechy; prafenomen; the law of polarity; philosophical masochism